Peningkatan Hasil Belajar Siswa Materi Permintaan Penawaran Harga Pasar Berbasis Karakter Menggunakan Model Pembelajaran Kooperatif Tipe Teams Game Tournaments Kolaborasi Media Kartu (Pendidikan Ekonomi, 2013)
This study aimed to determine the improvement of student learning outcomes dealt with Demand and  supply  and  market  prices  material  that  uses  character  based  learning,.  This  study  aimed  to know the students and teacher activities by using cooperative learning model with TGT type that is collaborated with media card.  This study is a classroom action research that done in three cycles. The subjects of this research are the students of VIII-A class of SMP Negeri 2 Kediri.   The result of the study shows that the students and teacher’s learning activities are good and the student learning mastery increases in three cycles.   Key  words:    Learning  Outcomes,  TGT,  Media  Cards,  demand  and  supply  and  market prices material